APPLICATION OF THE HOTS-BASED SCIENTIFIC LEARNING APPROACH TO THE SCIENCE LEARNING OUTCOMES OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Kartini, Tianesa; Satinem, Yohana; Lokaria, Eka (Widyagogik, 2022)
This study aims to determine the science learning outcomes of fifth grade students at SDN 57 Lubuklinggau after using a HOTS-based scientific learning approach. The method used is a quasi-experimental research method, with a pre-test-post-test group research design. The population in this study were all students of class V SDN 57 Lubuklinggau totaling 22 students who were the sample in the study. Data collection is done by giving a description of 6 questions. Data were analyzed using the z-test at a significant level of = 0,05. Based on the results of the post-test data analysis, it was found that zcount 5,50 and ztable 1,64 means Ho is rejected and Ha is accepted, meaning that the science learning outcomes of fifth grade students at SDN 57 Lubuklinggau after the implementation of the HOTS-based scientific learning approach are significantly complete. The average obtained is 77,65 and the percentage of the number of students who complete reaches 100%.